Pengaruh Artificial Intelligence, Kapabilitas Teknologi Informasi, Dan Pelatihan Karyawan Terhadap Efisiensi Proses Akuntansi Di Kantor Akuntan Publik Kota Malang - Lestari, Eny Endang; Dura, Justita (Universitas Multi Data Palembang, 2025)
This study aims to analyze the impact of Artificial Intelligence, information technology capabilities, and employee training on the efficiency of accounting processes in Public Accounting Firms in Malang City. This research uses a quantitative method with a survey approach, targeting a population of accounting staff in several Public Accounting Firms in the area. The results show that Artificial Intelligence and information technology capabilities significantly enhance accounting process efficiency through task automation and better data management. Employee training is essential for making new technologies work best. This study provides practical recommendations for Public Accounting Firms to improve technology adoption and employee training to achieve higher efficiency in accounting processes.